2014
DOI: 10.1186/1749-7221-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning reduces the severity of ischemia-reperfusion injury of peripheral nerve in rats

Abstract: Background and aimAllow for protection of briefly ischemic tissues against the harmful effects of subsequent prolonged ischemia is a phenomennon called as Ischemic Preconditioning (IP). IP has not been studied in ischemia-reperfusion (I/R) model of peripheral nerve before. We aimed to study the effects of acute IP on I/R injury of peripheral nerve in rats.Method70 adult male rats were randomly divided into 5 groups in part 1 experimentation and 3 groups in part 2 experimentation. A rat model of severe nerve is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…found that the microvascular clamp model was ineffective for vascular occlusion because of the delicate vascular structures of the rat ovaries . In another study, slip‐knot technique was found to be more effective compared with microvascular clamp in a rat model of peripheral nerve I/R injury . Although this technique may have some advantages including rapid release at the time of reperfusion without disruption of the pedicles and achieving complete vascular occlusion, the present method was also used in many I/R models.…”
Section: Discussionmentioning
confidence: 85%
“…found that the microvascular clamp model was ineffective for vascular occlusion because of the delicate vascular structures of the rat ovaries . In another study, slip‐knot technique was found to be more effective compared with microvascular clamp in a rat model of peripheral nerve I/R injury . Although this technique may have some advantages including rapid release at the time of reperfusion without disruption of the pedicles and achieving complete vascular occlusion, the present method was also used in many I/R models.…”
Section: Discussionmentioning
confidence: 85%
“…It was shown that the slip-knot technique was more effective compared with the microvascular clamp model in rat ovaries for an I/R injury study of peripheral nerves. Also, this technique had some advantages including rapid release at the time of reperfusion without disrupting the pedicles and achieving complete vascular occlusion [25]. Therefore, we preferred the slip-knot technique in the present rat ovary I/R injury study.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is considered to be one of the main causes of neural damage after injury. Recent study shows that the oxidative stress led to the functional recovery retardation in the peripheral nerve, which is characterized with the increased levels of free oxygen radicals . Previous studies both in vitro and in vivo have demonstrated that neurotrophins, including NGF, can change the expressions of certain antioxidant enzymes .…”
Section: Introductionmentioning
confidence: 99%
“…Recent study shows that the oxidative stress led to the functional recovery retardation in the peripheral nerve, 7 which is characterized with the increased levels of free oxygen radicals. 18,19 Previous studies both in vitro and in vivo have demonstrated that neurotrophins, including NGF, can change the expressions of certain antioxidant enzymes. 20,21 Therefore, we seek to examine the relationship between the oxidative stress and the microenvironment with different conduits after injury, and identify its effects on the nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%